Harris and the Sacred Cow: A Critique on Marvin Harris' Materialistic Theory on the Hindu India' Holiest Animal - Khatri, Prem K (Tribhuvan University Journal, 2011)
Not available. Key words: Materialistic Theory; Hindu; India; Holiest Animal Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 27-34 Uploaded date: 22 April, 2011